Konsep Pengembangan Pengaturan Sistem Pengawasan Pelaksanaan Jabatan Notaris di Indonesia - Purwanto (Fakultas Hukum Universitas Mulawarman, 2009)
The Controlling toward the implementation of Notary profession by effort of building and inspecting is done by the Minister of Law and Human Right of Indonesia by establing Notary Contoller Commission, the Notary Contoller Commission consists of Local Controller Commission, District Controller Commission and Central Controller Commission. The normative essential in the Direction of Implementation Duty of Notary Controller Commission is not completed with assessment system in the form of objective assessment instrument in inspecting Notary Commission Implementation, as the effect, the aspect of justice to the Notary whom inspected cannot be manifestated. In the effort to realize assessment system in inspecting Notary commission implementation oriented to the justice, it is necessary to formulate: (1) predication and criterion assessment in inspecting the Notary commission implementation, (2) instrument assessment in inspecting the Notary commission implementation, and (3) regulation and decission that establish the criterion, predication and instrument assessment in inspecting the Notary commission implementation.